Prognostic significance of isolated left anterior hemiblock and left axis deviation in the course of acute myocardial infarction. - Büyüköztürk, K (1977)
In 700 patients with acute myocardial infarction admitted to the intensive coronary care unit of our hospital, the incidence and significance of left anterior hemiblock and left axis deviation has been studied in the acute phase of disease. In 102 (14.6%) of the 700 patients, isolated left axis deviation (mean QRS axis-45 degrees) was found and 69 of them (9.9%) met the criteria of left anterior hemiblock. Of the 69 patients with left anterior hemiblock, 61 had acute anterior myocardial infarction, 5 had inferior infarction, and 3 had subendocardial infarction. The anterior hemiblock was transient in 5 patients, but persisted in 64. All patients with and without isolated left anterior hemiblock and left axis deviation were compared statistically with reference to mortality rate and the incidence of arrythmias; no significant difference was noted. However, in patients over the age of 65 and also in those with hypertension, the incidence of left axis deviation was significantly higher (P less than 0.05 and P less than 0.001, respectively). It was concluded that isolated left anterior hemiblock and left axis deviation occurring in the course of acute myocardial infarction no influence on the prognosis of acute myocardial infarction.